The mechanism of toxicity in HET-S/HET-s prion incompatibility. - Carolin Seuring; Jason Greenwald; Christian Wasmer; Roger Wepf; Sven J Saupe; Beat H Meier; Roland Riek (PLoS Biology)
The HET-s protein from the filamentous fungus Podospora anserina is a prion involved in a cell death reaction termed heterokaryon incompatibility. This reaction is observed at the point of contact between two genetically distinct strains when one harbors a HET-s prion (in the form of amyloid aggregates) and the other expresses a soluble HET-S protein (96% identical to HET-s). How the HET-s prion interaction with HET-S brings about cell death remains unknown; however, it was recently shown that this interaction leads to a relocalization of HET-S from the cytoplasm to the cell periphery and that this change is associated with cell death. Here, we present detailed insights into this mechanism in which a non-toxic HET-s prion converts a soluble HET-S protein into an integral membrane protein that destabilizes membranes. We observed liposomal membrane defects of approximately 10 up to 60 nm in size in transmission electron microscopy images of freeze-fractured proteoliposomes that were formed in mixtures of HET-S and HET-s amyloids. In liposome leakage assays, HET-S has an innate ability to associate with and disrupt lipid membranes and that this activity is greatly enhanced when HET-S is exposed to HET-s amyloids. Solid-state nuclear magnetic resonance (NMR) analyses revealed that HET-s induces the prion-forming domain of HET-S to adopt the β-solenoid fold (previously observed in HET-s) and this change disrupts the globular HeLo domain. These data indicate that upon interaction with a HET-s prion, the HET-S HeLo domain partially unfolds, thereby exposing a previously buried ∼34-residue N-terminal transmembrane segment. The liberation of this segment targets HET-S to the membrane where it further oligomerizes, leading to a loss of membrane integrity. HET-S thus appears to display features that are reminiscent of pore-forming toxins.